2018
DOI: 10.1016/j.bjm.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of leptospiral commercial vaccines on the protection against an autochtonous strain recovered in Brazil

Abstract: In swine and bovines, leptospirosis prevention and control is carried out via vaccination of susceptible animals using bacterins. However, the efficiency of leptospirosis vaccines has been questioned. This work aimed to investigate the potency of five leptospirosis vaccines sold commercially in Brazil, challenging the animals with one autochthonous strain of Leptospira, Canicola serovar, denoted LO4, isolated from swine. The standard protocol was followed, and renal carriers of Leptospira were identified among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
4
10
0
Order By: Relevance
“…Other than reduction of lethality, the ability to prevent transmission is a key parameter to determine the success and feasibility of a leptospiral vaccine. Whole-cell vaccines have shown divergent levels of protection against colonization in different species ( Sonada et al, 2018 ; Murray et al, 2013 ; Clough et al, 2018 ; Bolin and Alt, 2001 ). In our hamster model we observed a significant reduction of the bacterial burden in the kidney of vaccinated animals, without significant levels of protection.…”
Section: Discussionmentioning
confidence: 99%
“…Other than reduction of lethality, the ability to prevent transmission is a key parameter to determine the success and feasibility of a leptospiral vaccine. Whole-cell vaccines have shown divergent levels of protection against colonization in different species ( Sonada et al, 2018 ; Murray et al, 2013 ; Clough et al, 2018 ; Bolin and Alt, 2001 ). In our hamster model we observed a significant reduction of the bacterial burden in the kidney of vaccinated animals, without significant levels of protection.…”
Section: Discussionmentioning
confidence: 99%
“…Other than reduction of lethality, the ability to prevent transmission is a key parameter to determine the success and feasibility of a leptospiral vaccine. Whole-cell vaccines have shown divergent levels of protection against colonization in different species 26-29 . In our hamster model we observed a significant reduction of the bacterial burden in the kidney of vaccinated animals, without significant levels of protection.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of strains in Madagascar, Tanzania, Reunion and Brazil, such as L. borgpetersenii clade D (Figure 2), genetically distinct from any reference strains, has implications for the control and diagnosis of leptospirosis in the developing world. In Brazil, it has been demonstrated that the efficacy of commercial vaccines is poor in the face of autochthonous strain challenge (Sonada et al, 2018) and it is likely that commercial vaccines are likely to perform as poorly in Madagascar and other developing countries. Moreover, the inclusion of local isolates in antigen panels for serological assays, such as MAT, can dramatically increase the serological detection of infections (Mgode et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination of livestock is used to both improve productivity and to reduce zoonotic risk from livestock (Marshall and Chereshsky, 1996). However, recent studies have demonstrated that commercial leptospirosis vaccines may lack efficacy when challenged by autochthonous livestock strains in Brazil (Sonada et al ., 2018) and will not reduce human infections from serovars associated with wildlife (Thornley et al ., 2002). Therefore, to inform control measures, we used abattoir sampling and molecular methods to determine the prevalence and diversity of Leptospira in livestock in Madagascar and their phylogenetic relationship to Leptospira identified in livestock from similar studies in other developing countries.…”
Section: Introductionmentioning
confidence: 99%